2014
DOI: 10.1017/s0950268814002295
|View full text |Cite
|
Sign up to set email alerts
|

Toxins and virulence factors of enterotoxigenicEscherichia coliassociated with strains isolated from indigenous children and international visitors to a rural community in Guatemala

Abstract: SUMMARYDiarrhoea remains a common cause of illness in Guatemala, with children suffering most frequently from the disease. This study directly compared the frequency, enterotoxin, and colonization factor (CF) profiles of enterotoxigenic Escherichia coli (ETEC) strains isolated from children living in a rural community in Guatemala and from Western visitors to the same location during the same seasons, using similar detection methodologies. We found that ETEC accounted for 26% of severe cases of diarrhoea in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 35 publications
(45 reference statements)
4
17
0
Order By: Relevance
“…) and Guatemala (Torres et al . ) the trend was LT > ST > ST+LT. Global enteric multicenter study (GEMS) in several developing countries reported that ETEC strains with either ST or together with LT were associated with moderate to severe diarrhoea (Kotloff et al .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…) and Guatemala (Torres et al . ) the trend was LT > ST > ST+LT. Global enteric multicenter study (GEMS) in several developing countries reported that ETEC strains with either ST or together with LT were associated with moderate to severe diarrhoea (Kotloff et al .…”
Section: Discussionmentioning
confidence: 85%
“…In ETEC isolates from indigenous children and international visitors to a rural community in Guatemala, a large percentage analysed for CFs lacked a detectable CF (Torres et al . ). These results indicated the possibility of the existence of other CFs that are yet to be identified.…”
Section: Discussionmentioning
confidence: 97%
“…12 A challenge to vaccine development is the temporal, regional, and population-specific variabilities in ETEC CFs expressed. 13 There is heterogeneity in the ETEC strains circulating among the pediatric population in developing countries and the strains infecting traveler's to that country as supported in a recent study in Guatemala that toxins and CF do not completely overlap among indigenous children and adult travelers, 14 and is further supported by the systematic review performed by Isidean and others. 6 Thus, a vaccine for ETEC needs to have broad coverage for both travelers to, and pediatric populations in the developing world.…”
Section: Introductionmentioning
confidence: 84%
“…[1][2][3] These very common infections are estimated to cause some 25,000 child deaths annually and contribute to child malnutrition. 1 Besides, ETEC is the leading cause of diarrhea among tourists 4,5 and military personnel 6,7 staying in ETEC endemic regions. Deaths associated with ETEC infection are declining worldwide; nevertheless, morbidity remains high.…”
Section: Introductionmentioning
confidence: 99%